1999
DOI: 10.1163/22941932-90000691
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Chronologies from Teak in Northern Thailand and their Climatic Signal

Abstract: Five teak trees in northem Thailand were selected for the study of vessels in terms of dendroclimatology. The tree rings were divided into earlywood and latewood, and fourparameters (average vessel area, average vessel diameter, average conductive area, and vessel density) were measured by automatie image analysis technique to obtain 50-year (1947-1996) time series. Two questions were addressed: 1) How strongly are the vessel characteristics related to climate and 2) are these relationships different from thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 0 publications
5
31
0
2
Order By: Relevance
“…Cell anatomical features of tree rings have already been shown to encode environmental signals (e.g., [9][10][11][12][13]). Furthermore, important advancements over recent years in monitoring tree-growth at higher time resolutions are showing that it is possible to mechanistically link the environment with wood formation and structure [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Cell anatomical features of tree rings have already been shown to encode environmental signals (e.g., [9][10][11][12][13]). Furthermore, important advancements over recent years in monitoring tree-growth at higher time resolutions are showing that it is possible to mechanistically link the environment with wood formation and structure [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on several species such as Quercus macrocarpa Michx. (Woodcock 1989), Fagus sylvatica L. (Sass and Eckstein 1995), Tectona grandis L.f. (Pumijumnong and Park 1999), Castanea sativa Mill. (Fonti and García-González 2004) and Prosopis flexuosa DC (Giantomasi et al 2009) showed the importance of climatic conditions on vessel ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…vessels, and Panyushkina et al (2003) were able to identify a temperature signal from the annual variation of the lumen diameter and wall thickness from tracheids of Larix cajanderi Mayr. For ring-porous tree species, the mean vessel area (MVA) in the earlywood is a useful variable to provide information about past climate which is not equally well retained by the radial increment (e.g., Pumijumnong and Park 1999;García-González and Eckstein 2003;Fonti and García-González 2004).…”
Section: Introductionmentioning
confidence: 99%